2018
DOI: 10.18235/0001794
|View full text |Cite
|
Sign up to set email alerts
|

Educación financiera y previsional a través del taller Ahorra desde Ahora: Evidencia de una evaluación de impacto en Chile

Abstract: Los sistemas de pensiones de contribución definida como el chileno trasladan gran parte de los riesgos asociados al sistema pensional al trabajador. Por lo tanto, para su buen funcionamiento estos sistemas requieren de una comprensión profunda de la población sobre conceptos financieros y previsionales. En la literatura hay consenso de que el nivel de educación financiera previsional es bajo (Lusardi y Mitchell, 2014). Este estudio mide el impacto de uno de los principales esfuerzos en materia de educación pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
(5 reference statements)
0
2
0
1
Order By: Relevance
“…Even when the treatment is less intensive, the provision of financial education while in high school is effective. Bosch et al (2018) experimentally measured the impact of a one-and-a-half-hour workshop imparted by the National Association of Pension Fund Managers in Chile and found a large and significant effect two months later on financial and pension knowledge among students in technical high schools.…”
Section: Box 4 Financial Education In High Schools Can Foster Financi...mentioning
confidence: 99%
See 1 more Smart Citation
“…Even when the treatment is less intensive, the provision of financial education while in high school is effective. Bosch et al (2018) experimentally measured the impact of a one-and-a-half-hour workshop imparted by the National Association of Pension Fund Managers in Chile and found a large and significant effect two months later on financial and pension knowledge among students in technical high schools.…”
Section: Box 4 Financial Education In High Schools Can Foster Financi...mentioning
confidence: 99%
“…Although studies that can identify a causal link between financial education and trust in financial institutions are quite scarce, the IDB Group has been able to generate promising evidence on this front. For example, Bosch et al (2018) found that the delivery of financial education lessons in high school led not only to an increase in financial literacy, but also to an increase in trust in pension funds and the pension system as a whole in a follow-up survey two months after the course.…”
Section: Financial Education Can Also Increase Trust In Financial Ins...mentioning
confidence: 99%
“…Este rubro en realidad impacta el resto de los beneficios descritos debido al conocimiento que brinda lo que a su vez formará usuarios de los sistemas financieros más analíticos, exigentes y perspicaces los instrumentos y productos que les ofrecen. Sobre este punto Bosch et al (2018) con el fin de evaluar el impacto de recibir educación financiera como previsión para el largo plazo encuentran que sus conocimientos financieros se fortalecen ampliamente, aunque no les es posible brindar resultados concluyentes en cuanto a la traducción de ello hacia mejoras en el estado financiero personal.…”
Section: Análisis De Los Beneficios De La Educación Financieraunclassified